2023
DOI: 10.2340/actadv.v103.5087
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Screening Practices and Statin Prescription Habits in Patients with Psoriasis among Dermatologists, Rheumatologists and Primary Care Physicians

Abstract: Patients with psoriasis have a higher prevalence of cardiovascular risk factors. This study evaluated cardiovascular screening practices and statin prescribing habits among dermatologists, rheumatologists and primary care physicians (PCPs) through an online questionnaire, which was distributed through the Spanish scientific societies of the above-mentioned specialties. A total of 299 physicians (103 dermatologists, 94 rheumatologists and 102 PCPs) responded to the questionnaire. Of these, 74.6% reported screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Health Problems of Civilization eISSN: 2354-0265, ISSN: 2353-6942 knowledge of screening recommendations in psoriasis patients [3]. This study found that more than 60% of primary care physicians were unaware of psoriasis being associated with CVD [3].…”
Section: Interestingly a Spanish Study Assessed The Connections Betwe...mentioning
confidence: 78%
See 1 more Smart Citation
“…Health Problems of Civilization eISSN: 2354-0265, ISSN: 2353-6942 knowledge of screening recommendations in psoriasis patients [3]. This study found that more than 60% of primary care physicians were unaware of psoriasis being associated with CVD [3].…”
Section: Interestingly a Spanish Study Assessed The Connections Betwe...mentioning
confidence: 78%
“…Recent studies have identified that psoriasis and CVD have various common pathogenic pathways including genetic factors, inflammatory pathways, adipokine secretion, insulin resistance, lipoproteins, angiogenesis and oxidative stress [3]. Reasons for increased CVD risk include both increased systemic inflammation caused by psoriatic lesions, usually covering large areas of the skin and the fact that psoriasis is associated with an increased incidence of modifiable cardiovascular risk factors such as obesity, smoking, hypertension, diabetes mellitus, dyslipidemia, metabolic syndrome and a sedentary lifestyle [3]. The study by Karbach et al [4] found that psoriatic patients with heart attacks were on average 5 years younger than heart attack patients without psoriasis.…”
Section: Dear Editormentioning
confidence: 99%
“…Traditional prediction systems based on classical CVRFs, underestimate the actual CV risk of patients with psoriasis and other chronic inflammatory states. 8 34 There is a lack of markers that allow us to adequately predict those patients who will develop CV disease. In this scenario, numerous publications have emerged recently highlighting the value of detecting subclinical atherosclerosis through various imaging tests as a tool to overcome this gap.…”
Section: Discussionmentioning
confidence: 99%
“…The screening for CVD risk factors among psoriasis patients is often inadequate, leading to suboptimal management. 133 This issue is compounded by dermatologists and rheumatologists’ hesitance to prescribe statins, 4 highlighting the need for better coordination and clear delineation of responsibilities among healthcare providers. A survey-based study by Barbieri et al reported optimistic views from both dermatologists and patients regarding the adoption of a care model led by dermatologists or rheumatologists for CVD prevention.…”
Section: Impact Of Psoriasis Treatments On Cardiovascular Healthmentioning
confidence: 99%
“… 3 Multiple questionnaire-based studies have revealed that surveyed physicians, including dermatologists, rheumatologists, cardiologists and primary care physicians, often fail to conduct comprehensive screenings for hypertension, dyslipidemia, smoking, and diabetes mellitus, with more than half of primary care physicians unaware of the connection between psoriasis and cardiovascular disease. 4 , 5 A recent Delphi consensus has affirmed the significance of cardiovascular disease as a crucial comorbidity in patients with psoriatic disease. 6 It emphasized the need for evaluation in clinical trials, marking this as an area warranting further investigation.…”
Section: Introductionmentioning
confidence: 99%